Synovial Cysts in the Temporomandibular Joint: a Case Report and Critical Review of the Literature - Ynn Maribo; Kasper Stokbro; Esben Aagaard; Stine Rosenkilde Larsen; Torben Thygesen (eJournal of Oral Maxillofacial Research, 2019)
Background: Synovial cysts of the temporomandibular joint are rare and treatment is based on consensus from cases reporting unilateral successful outcomes. A patient with a synovial cyst is presented, treated with successful surgical excision of the cyst, but without remission of joint symptoms. Furthermore, the case is supplemented by a critical, literature review.